Study on the Performance of Ball Mill with Liner Structure based on DEM - Zhanfu Li; Yaokun Wang; Kunyuan Li; Wenyu Lin; Xin Tong (Journal of Engineering and Technological Sciences, 2018)
This study used the discrete element method (DEM), which is effective and popular for solving the problem of granular systems simulating the motion of particles in a ball mill in different structural forms and at different rotational speeds. Firstly, simulations of five kinds of lifters (triangular, trapezoidal, rectangular, ladder and hemispherical) were set up. The results were as follows: when the rectangular lifter was selected as mill liner, the ball mill efficiency was significantly high. The breaking performance of the hemispherical lifter and the ladder lifter was poor, because the main pattern of motion was grinding rather than impact breakage. Secondly, the effects of the height"“width ratio of the rectangular lifter, the height of the lifter and the number of lifters on the working efficiency of the ball mill were studied. It was found that a number of rectangular lifters of 12 and a height-width ratio of 3:1 produced the best results. The best height of the rectangular lifter was about 13 mm. Lastly, displacement, stress and deformation were analyzed using DEM coupled with a finite element method (FEM). The purpose was to design the geometrical lifter structure and to improve the performance of the ball mill.